High‐dose IVIG plus cangrelor platelet "anesthesia" during urgent heparin‐CPB in a patient with recent SRA‐negative HIT‐thrombosis with persisting platelet‐activating antibodies. Issue 6 (23rd July 2020) - Koster, Andreas; Nazy, Ishac; Birschmann, Ingvild E.; Smith, James W.; Sheppard, Jo‐Ann I.; Warkentin, Theodore E.
Abstract: In a high‐risk patient with subacute heparin‐induced thrombocytopenia (HIT) type A (platelet count recovery following acute HIT but with persisting platelet‐activating antibodies), in whom urgent cardiac surgery was required, a key clinical question arose: could intraoperative heparin be given safely with "platelet anesthesia" provided with high‐dose intravenous immunoglobulin (IVIG) plus cangrelor (ultra‐short‐acting antiplatelet agent)? This approach proved successful, without unexpected postoperative thrombocytopenia or thromboembolism. In vitro studies confirmed that both IVIG and cangrelor contributed to perioperative inhibition of HIT antibody‐induced platelet activation. Interestingly, despite the patient testing strongly positive in 4 HIT immunoassays (latex immunoturbidimetric assay and 3 enzyme‐immunoassays), the serotonin‐release assay (SRA) was consistently negative. Nevertheless, platelet‐activating HIT antibodies were detectable using modified (platelet factor 4–enhanced) SRA. Our protocol of heparin rechallenge following IVIG/cangrelor provides both intraoperative and early postoperative inhibition of HIT antibody‐induced platelet activation and is applicable to patients with circulating functional HIT antibodies requiring urgent heart surgery, including those with "SRA‐negative HIT."